Owen Williams - Yeomans, David T. (Thomas Telford, 2001)
Sir Owen Williams' influence on the architecture of the first half of the 20th century stemmed from a demonstration of what a functionalist approach to architecture could achieve. This volume traces the development of Williams' ideas and assesses his influence on architecture.
Keywords: Williams, Owen, -- Sir, -- 1890-1969 -- Criticism and interpretation.; Bridges -- Design and construction.; Commercial buildings -- Design and construction.; elektronické knihy; electronic books